Lithium-copper composite belt and preparation method and equipment thereof
By tying the copper foil into holes, it forms spikes or protrusions and embedded in the lithium foil. Combined with mechanical roller pressing technology, the problem of poor bonding of the lithium copper composite belt is solved, and a batch of lithium copper composite belts with high composite strength is achieved Production avoids the problems of lithium metal power outage and copper foil breakage.
Patent Information
- Application Number
- CN202411405453.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2020-07-07
- Publication Date
- 2025-01-03
AI Technical Summary
It is difficult to mass produce high-composite strength lithium-copper composite tapes with copper foil thickness of less than 12 μm and lithium foil thickness of less than 100 μm, and the problem of failure of lithium foil and copper foil to cause the metal lithium power outage.
Using structural inlay concept, the copper foil is drilled to form spikes or protrusions, embedded in the lithium foil, and a high composite strength lithium copper composite belt is formed through mechanical roller pressing composite technology, using continuous production method of roll-to-roll Prepare with specific equipment.
The high composite strength of lithium copper composite belt is achieved, the problem of lithium metal power outage is avoided, and the technical bottleneck of mass production of high composite belts with copper foil thickness below 12μm and lithium foil thickness below 100μm is broken, and the roller pressure is reduced. , avoiding the problem of copper foil breakage.
Smart Images

Figure CN119252841A_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent with application date of July 7, 2020, application number 202010645172.X, and invention name "Lithium-copper composite strip and preparation method and equipment thereof". Technical Field
[0002] The present invention relates to the field of energy storage technology, and in particular to a lithium-copper composite belt with high composite strength and a preparation method and equipment thereof. Background Art
[0003] Lithium batteries are widely used in aerospace, computers, mobile communication equipment, robots and electric vehicles due to their high energy density, long cycle life and wide applicable temperature range. At present, the commonly used negative electrode material for lithium batteries is graphite material. The specific capacity of graphite negative electrode is 372mAh / g. The energy density of traditional graphite negative electrode system has no much room for improvement. The theoretical specific capacity of metallic lithium is 3860mAh / g, and the redox potential is low. Lithium metal is considered by the industry to be the ultimate negative electrode solution for high energy density batteries. Therefore, the preparation of composite metal lithium strips (especially ultra-thin composite metal lithium strips) has become a current research hotspot.
[0004] At present, the methods for preparing composite metal lithium belts at home and abroad mainly include: (1) Wet lithium replenishment: dissolving lithium powder in an organic solvent and replenishing lithium by spraying / dripping the solution. This method has complex procedures; high dependence on lithium powder and high lithium powder preparation cost; a large amount of organic solvent volatilizes during the drying process; the thickness of the lithium layer in the prepared lithium-copper composite belt is usually above 100μm. (2) Mechanical rolling composite method is used to prepare lithium-copper composite belt. This method is simple to produce, with high precision and low investment cost; but due to the great difference in mechanical properties between lithium and copper metals, the lithium-copper composite belt produced when the rolling pressure is small often has insufficient bonding ability, which causes the metal lithium to lose power during battery use, affecting the battery use effect and life; and when the rolling pressure is large, the copper foil is often broken, resulting in the product being unusable. Therefore, this method is usually used to produce lithium-copper composite belts with a copper foil thickness of more than 12μm.
[0005] In summary, the industry has achieved mass production of lithium-copper composite tapes with a lithium layer thickness of more than 100μm and a copper foil thickness of more than 12μm. However, the mass production of high-composite-strength lithium-copper composite tapes with a copper foil thickness of less than 12 microns and a lithium foil thickness of less than 100μm has always been a bottleneck that needs to be solved in the industry. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the above-mentioned technology and provide a method and equipment for preparing a lithium-copper composite strip with high composite strength to solve the problem of weak adhesion between lithium foil and copper foil and avoid the problem of power failure of lithium metal during battery operation; on the other hand, the method provided by the present invention can solve the production problem of ultra-thin lithium-copper composite strip with high composite strength, making it possible to produce lithium-copper composite strip with high composite strength having a copper foil thickness of less than 12 μm and a lithium foil thickness of less than 100 microns.
[0007] One aspect of the present invention is to provide a lithium-copper composite belt, the lithium-copper composite belt comprising:
[0008] Copper foil, the copper foil having a thickness of 2-6 μm, and being divided into a perforated area and a non-perforated area, wherein the perforated area has a plurality of pores, the pore spacing is 0.5-2 mm, the pore diameter is 0.05-0.5 mm, and the edges of the pores have copper foil remaining in the form of spikes or protrusions; and
[0009] A lithium foil is laminated to at least one surface of the copper foil and covers at least a portion of the punching area, wherein the spikes or protrusions are embedded in the lithium foil, and the lithium foil has a thickness of 20-50 μm.
[0010] The present invention adopts the concept of structural inlay, and the spikes or protrusions formed after the copper foil is punched are embedded in the lithium foil during roll-pressing and compounding to form a mutually inlaid structure. Therefore, the lithium-copper composite belt provided by the present invention has a very high composite strength.
[0011] In the present invention, the copper foil preferably satisfies at least one of the following conditions:
[0012] The copper foil has a width of 30-200 mm;
[0013] The width of the copper foil is not less than the width of the lithium foil;
[0014] In the width direction of the copper foil, the punched area is centered, and the non-punched areas are located on both sides of the punched area.
[0015] Optionally, the plurality of pores are evenly distributed in the perforated area to provide uniform lithium-copper composite strength.
[0016] Optionally, the width of the perforated area on the copper foil differs from the width of the lithium foil by no more than 10 mm, and preferably the width of the perforated area on the copper foil is the same as the width of the lithium foil.
[0017] Optionally, the lithium foil has a width of 20-180 mm.
[0018] Optionally, at least one side of the copper foil is laminated with lithium foil; optionally, both sides of the copper foil are laminated with lithium foil.
[0019] Another aspect of the present invention provides a method for preparing a lithium-copper composite strip, the method comprising:
[0020] Prepare a lithium foil with a thickness of 20-50 μm and a copper foil with a thickness of 2-6 μm;
[0021] Punching holes in the copper foil;
[0022] The lithium foil and copper foil are composited together by mechanical rolling.
[0023] Optionally, before the copper foil is punched, the copper foil is dried.
[0024] The preparation method of the lithium copper composite strip of the present invention is a roll-to-roll continuous production method, which may specifically include the following steps:
[0025] Step 1: Dry the copper foil. Place the copper foil in a vacuum oven and set the drying temperature to 50-160°C and the drying time to 0.5-20h. The preferred drying temperature is 50-80°C and the drying time is 0.5-8h.
[0026] Step 2: Punch the copper foil. Punch the copper foil mechanically so that the original copper foil remains on the copper foil in the form of spikes or protrusions at the pores of the copper foil. The mechanical punching method can be a micro-needle roller or the like.
[0027] Step 3: Roll-compress the copper foil and the lithium foil. The copper foil and the lithium foil are put into a roller press together for pressure compounding, and the rolling pressure range is 0.02MPa to 5MPa, and the preferred pressure range is 0.1MPa to 1MPa.
[0028] Optionally, the rollers of the roller press are subjected to anti-sticking treatment.
[0029] Optionally, the anti-sticking treatment is carried out by providing an anti-sticking layer (eg polyethylene, polyoxymethylene, silicone polymer, ceramic, etc.) on the roller.
[0030] Optionally, the anti-sticking treatment is carried out by applying an anti-sticking agent (such as white oil) on the roller.
[0031] Optionally, the anti-sticking treatment method is to arrange an anti-sticking film (for example, a biaxially oriented polypropylene film (BOPP) anti-sticking film, etc.) between the lithium foil and the roller during the rolling process.
[0032] Another aspect of the present invention also provides a device for preparing the above-mentioned lithium-copper composite belt with high composite strength, the device comprising:
[0033] Lithium foil unwinding assembly, used for unwinding lithium foil coils;
[0034] Copper foil unwinding component, used for unwinding copper foil coils;
[0035] A copper foil punching assembly, comprising a micro-needle roller and a fine-tuning mechanism, for punching holes in the unwound copper foil;
[0036] Roller press, used for pressure lamination of punched copper foil and lithium foil;
[0037] The composite tape winding assembly is used to wind up the composite lithium-copper composite tape for use, and the composite tape winding assembly may also optionally include a protective film unwinding assembly.
[0038] Optionally, the lithium foil / copper foil unwinding assembly further includes a tension control assembly or a deviation correction assembly.
[0039] Optionally, the composite tape winding assembly further includes a tension control assembly or a deviation correction assembly.
[0040] Optionally, the rollers of the roller press are provided with an anti-stick coating.
[0041] The beneficial effects of the present invention include:
[0042] 1. The idea of structural inlay is adopted to make the copper foil and lithium foil form a mutually embedded structure with extremely high composite strength, thus avoiding the problem of metal lithium power failure caused by the loose composite of lithium foil and copper foil during the use of the lithium-copper composite belt.
[0043] 2. The conventional pressure bonding method of lithium foil and copper foil is transformed into a structural inlay bonding method, so that the bonding process only requires a small rolling pressure, avoiding the problem of copper foil wrinkling or breaking due to excessive pressure. Therefore, the technical bottleneck of mass production of high-composite strength lithium-copper composite strips with a copper foil thickness of less than 12μm and a lithium foil thickness of less than 100μm has been broken. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 A schematic diagram of the copper foil after punching holes in the present invention;
[0045] Figure 2 A schematic structural diagram of a lithium-copper composite belt with high composite strength according to the present invention;
[0046] Figure 3 A process flow chart for preparing a high-strength lithium-copper composite belt according to the present invention;
[0047] Figure 4 A schematic diagram of a device for preparing a high-strength lithium-copper composite strip according to the present invention;
[0048] Figure 5 for Figure 4 A schematic diagram of the microneedle roller in the copper foil hole punching assembly;
[0049] Figure 6for Figure 5 A schematic diagram of the microneedle sheet;
[0050] Description of reference numerals:
[0051] C: copper foil, C0: unpunched area, C1: punched area, C10: hole,
[0052] C11: spikes or protrusions, L1: upper lithium foil, L2: lower lithium foil, 10: copper foil unwinding assembly,
[0053] 20: support roller, 30: copper foil punching assembly, 31: microneedle roller, 310: microneedle sheet,
[0054] 311: spacing adjustment sheet, 32: fine adjustment mechanism, 40: lithium foil unwinding assembly, 50: roller press,
[0055] 51: roller, 52: anti-sticking layer, 60: deviation correction mechanism, 70: composite belt winding mechanism,
[0056] 80: protective film unwinding assembly, LC: lithium copper composite tape, P: protective film. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0058] Figure 1 A schematic diagram showing the copper foil after punching holes in the present invention is shown. Figure 2 A schematic diagram of the structure of a lithium-copper composite belt with high composite strength provided by the present invention is shown. Figure 1 As shown, the copper foil C usually has a punched area C1 and an unpunched area C0. The only difference between the unpunched area C0 and the punched area C1 is whether the punching process is performed. In the lithium-copper composite belt with high composite strength of the present invention, the lithium foils (L1, L2) are all composited to the punched area C1 of the copper foil C.
[0059] The punching area C1 of the copper foil C has been punched, so that the copper foil C has a hole C10, which is usually a through hole or a non-through hole. After the punching process, a spike or protrusion C11 is formed on the copper foil C. Figure 2 As shown, the spikes or protrusions C11 on the copper foil C are embedded into the upper lithium foil L1 and the lower lithium foil L2 when the copper foil is composited with the lithium foil, forming a firm embedded structure.
[0060] Figure 3A process flow chart of the present invention for preparing a high-strength lithium-copper composite strip is shown, which includes combining lithium foil and copper foil together by mechanical rolling. Specifically, the following steps are included:
[0061] Step 1: Dry the copper foil. Place the copper foil in a vacuum oven and set the drying temperature to 50-160°C and the drying time to 0.5-20h. The preferred drying temperature is 50-80°C and the drying time is 0.5-8h.
[0062] Step 2: Punch the copper foil. Punch the copper foil mechanically so that the original copper foil remains on the copper foil in the form of spikes or protrusions at the pores of the copper foil. The mechanical punching method can be a micro-needle roller or the like.
[0063] Step 3: Roll-compress the copper foil and the lithium foil. The copper foil and the lithium foil are put into a roller press together for pressure compounding, and the rolling pressure range is 0.02MPa to 5MPa, and the preferred pressure range is 0.1MPa to 1MPa.
[0064] Figure 4 A schematic diagram of a device for preparing a high-strength lithium-copper composite belt according to the present invention is shown. Figure 5 for Figure 4 A schematic diagram of the microneedle roller in the copper foil hole punching assembly. Figure 6 for Figure 5 A schematic diagram of the microneedle sheet.
[0065] like Figure 4-6 As shown, the device for preparing a high composite strength lithium-copper composite belt of the present invention comprises:
[0066] Copper foil unwinding assembly 10, support roller 20 (may be multiple), copper foil punching assembly 30, lithium foil unwinding assembly 40, roller press 50, deviation correction mechanism 60, composite tape winding assembly 70 and protective film unwinding assembly 80.
[0067] The copper foil unwinding assembly 10 includes an unwinding shaft for fixing and unwinding the copper foil, and in some embodiments may also include a deviation correction mechanism or a tension control mechanism. The support roller 20 has the function of supporting the copper foil, the lithium foil and the lithium-copper composite strip.
[0068] The copper foil punching assembly 30 comprises a microneedle roller 31 and a fine adjustment mechanism 32. The microneedle roller 31 is assembled from a plurality of microneedle sheets 310 and a spacing adjustment sheet 311 (see Figure 5), and the spacing between each microneedle sheet 310 is determined by the thickness of the spacing adjustment sheet 311; the fine-tuning mechanism 32 can drive the microneedle roller 31 to move along the normal direction of the copper foil strip (perpendicular to the plane where the copper foil is located), thereby controlling the puncture depth and puncture diameter. The roller press 50 includes a roller 51, and the roller 51 is provided with an anti-sticking layer. The outlet end of the roller press 50 is provided with a correction mechanism 60, a composite tape winding assembly 70 and a protective film unwinding assembly 80, and the correction mechanism 60 is used to correct the composite tape to ensure neat winding.
[0069] The specific use process and method are as follows: fix the copper foil C to the copper foil unwinding assembly 10, and after unwinding, the copper foil C will pass through the support roller 20, the copper foil punching assembly 30, and the roller press 50 in sequence; fix the upper lithium foil L1 and the lower lithium foil L2 to the lithium foil unwinding assembly 40, and pass through the roller press 50 after unwinding; the upper lithium foil L1, the lower lithium foil L2 and the copper foil C are rolled by the roller 51 of the roller press 50 to form a lithium copper composite belt LC. After rolling and compounding, the lithium copper composite belt LC passes through the correction mechanism 60 and is rolled by the composite belt winding assembly 70, and the lithium copper composite belt LC is rolled together with the protective film P.
[0070] The lithium-copper composite belt with high composite strength and the preparation method thereof of the present invention are further described below in conjunction with specific embodiments.
[0071] Example 1
[0072] A method for preparing a lithium-copper composite belt with high composite strength comprises the following steps:
[0073] 1. A copper foil with a thickness of 12 μm and a width of 100 mm was placed in a vacuum oven for drying at a temperature of 80°C for 1 h.
[0074] 2. Punch holes in the copper foil, with a hole diameter of 0.2 mm, a hole spacing of 1 mm, and a total hole width of 60 mm.
[0075] 3. Two lithium strips with a thickness of 50 μm and a width of 60 mm were placed on both sides of the copper foil and rolled using a roller press. The rolling pressure was 1 MPa and the roll gap size was 108 μm to obtain a lithium-copper composite strip with a high composite strength and double-sided lithium coating of about 111 μm in thickness.
[0076] Example 2
[0077] A method for preparing a lithium-copper composite belt with high composite strength comprises the following steps:
[0078] 1. A copper foil with a thickness of 6 μm and a width of 100 mm was placed in a vacuum oven for drying at a temperature of 80°C for 1 h.
[0079] 2. Punch holes in the copper foil, with a hole diameter of 0.2 mm, a hole spacing of 1 mm, and a total hole width of 60 mm.
[0080] 3. Two lithium strips with a thickness of 20 μm and a width of 60 mm were placed on both sides of the copper foil and rolled using a roller press. The rolling pressure was 0.5 MPa and the roll gap size was 44 microns to obtain a lithium-copper composite strip with a high composite strength and a double-sided lithium coating of about 46 μm in thickness.
[0081] Comparative Example 1
[0082] The difference from Example 1 is that the preparation method of this comparative example does not perform hole punching treatment on the copper foil, and includes the following steps:
[0083] 1. A copper foil with a thickness of 12 μm and a width of 100 mm was placed in a vacuum oven for drying at a temperature of 80°C for 1 h.
[0084] 2. Two lithium strips with a thickness of 50 μm and a width of 60 mm were placed on both sides of the copper foil and rolled using a roller press. The rolling pressure was 1 MPa and the roller gap size was 108 μm to obtain a lithium-copper composite strip with a thickness of about 110 μm and lithium-coated on both sides.
[0085] Comparative Example 2
[0086] The difference from Example 2 is that the preparation method of this comparative example does not perform hole punching treatment on the copper foil, and includes the following steps:
[0087] 1. A copper foil with a thickness of 6 μm and a width of 100 mm was placed in a vacuum oven for drying at a temperature of 80°C for 1 h.
[0088] 2. Two lithium strips with a thickness of 20 μm and a width of 60 mm were placed on both sides of the copper foil and rolled using a roller press. The rolling pressure was 0.5 MPa and the roller gap size was 44 microns to obtain a lithium-copper composite strip with a high composite strength and double-sided lithium coating of about 45.5 μm in thickness.
[0089] Comparative Example 3
[0090] The difference from Example 2 is that the preparation method of this comparative example does not perform a hole punching treatment on the copper foil, the rolling pressure is 1 MPa, and includes the following steps:
[0091] 1. A copper foil with a thickness of 6 μm and a width of 100 mm was placed in a vacuum oven for drying at a temperature of 80°C for 1 h.
[0092] 2. Two lithium strips with a thickness of 20 μm and a width of 60 mm were placed on both sides of the copper foil and rolled using a roller press. The rolling pressure was 1 MPa and the roller gap size was 44 microns to obtain a lithium-copper composite strip with a high composite strength and a double-sided lithium coating of about 45 μm in thickness.
[0093] The lithium-copper composite tapes in Examples 1-2 of the present invention and Comparative Examples 1-3 were subjected to water washing treatment and peel strength measurement.
[0094] The steps of water washing treatment are: take a 1m long lithium copper composite tape sample, wash it to remove the lithium foil on the lithium copper composite tape, and then observe whether the copper foil is continuous. The steps of peel strength measurement are: cut the lithium-copper composite tape lithium-copper coated part into 20x20mm blocks, and then fix the two sides of the lithium copper composite tape on the two fixtures of the peel strength tester to perform a 180-degree peel test.
[0095] The measurement results are shown in Table 1.
[0096] Table 1 Test results of lithium copper composite strips obtained in the examples and comparative examples
[0097]
[0098] As can be seen from Table 1, the copper foil of Example 1-2 of the present invention is subjected to a hole-punching treatment and then rolled to obtain a lithium-copper composite strip with lithium on both sides. The copper foil is continuous and wrinkle-free, and the lithium foil and the copper foil cannot be peeled off, and have extremely high composite strength. Although Comparative Example 1-2 can obtain a lithium-copper composite strip with lithium on both sides, its peeling force is too small and can be easily peeled off, which can easily lead to the problem of power failure of metallic lithium during the use of the battery. Comparative Example 3 increases the rolling pressure to obtain a product with slightly improved peeling force, but the copper foil is partially broken, and it is difficult to distinguish whether the copper foil is broken without washing to remove the metallic lithium. It is very easy to be regarded as a qualified product, resulting in a failure of the battery to be used.
[0099] It should be understood that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium-copper composite belt, characterized in that: The lithium-copper composite belt comprises: Copper foil, the copper foil having a thickness of 2-6 μm, and being divided into a perforated area and a non-perforated area, wherein the perforated area has a plurality of pores, the pore spacing is 0.5-2 mm, the pore diameter is 0.05-0.5 mm, and the edges of the pores have copper foil remaining in the form of spikes or protrusions; and A lithium foil is laminated to at least one surface of the copper foil and covers at least a portion of the punching area, wherein the spikes or protrusions are embedded in the lithium foil, and the lithium foil has a thickness of 20-50 μm.
2. The lithium-copper composite belt according to claim 1, characterized in that: The copper foil satisfies at least one of the following conditions: The copper foil has a width of 30-200 mm; The width of the copper foil is not less than the width of the lithium foil; In the width direction of the copper foil, the punched area is centered, and the non-punched areas are located on both sides of the punched area.
3. The lithium-copper composite belt according to claim 1, characterized in that: The width of the punching area differs from the width of the lithium foil by no more than 10 mm.
4. The lithium-copper composite belt according to claim 1, characterized in that: The width of the punching area is the same as the width of the lithium foil.
5. The lithium-copper composite belt according to claim 1, characterized in that: The lithium foil has a width of 20-180 mm.
6. The method for preparing the lithium-copper composite tape according to any one of claims 1 to 5, characterized in that: The method comprises: Prepare a lithium foil with a thickness of 20-50 μm and a copper foil with a thickness of 2-6 μm; Punching holes in the copper foil; The lithium foil and copper foil are composited together by mechanical rolling.
7. The preparation method according to claim 6, characterized in that: The method is a roll-to-roll continuous production method.
8. An apparatus used in the preparation method according to claim 6 or 7, characterized in that: The device comprises: Lithium foil unwinding assembly, used for unwinding lithium foil coils; Copper foil unwinding component, used for unwinding copper foil coils; A copper foil punching assembly, comprising a micro-needle roller and a fine-tuning mechanism, for punching holes in the unwound copper foil; Roller press, used for pressure lamination of punched copper foil and lithium foil; The composite tape winding assembly is used to wind up the composite lithium-copper composite tape; the composite tape winding assembly also includes a protective film unwinding assembly.
9. The device according to claim 8, characterized in that The lithium foil unwinding assembly or the copper foil unwinding assembly further includes a tension control assembly or a deviation correction assembly; The composite tape winding assembly also includes a tension control assembly or a deviation correction assembly.
10. The device according to claim 8, characterized in that The rollers of the roller press are provided with an anti-stick coating.
Citation Information
Cited By
Metal-lithium composite belt and preparation method thereof
CN120033212A
